2021
DOI: 10.1002/celc.202100712
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation of Iron Porphyrin from an Equilibrium Solution with Diazonium‐Functionalised Axial Ligand: Dependence of Film Composition on Grafting Potential

Abstract: In dichloromethane solution, tetraphenylporphyrin iron (III) chloride (FeTPPCl) and 4‐(1H‐Imidazol‐1‐yl)aniline (Im‐Ph‐NH2) exist in equilibrium with axially‐coordinated [FeTPP(Im‐Ph‐NH2)n]+ (n=1 and 2). After in situ diazotisation of Im‐Ph‐NH2, electroreduction of the diazonium ion leads to deposition of a film incorporating [FeTPP(Im‐Ph)2]+ and uncoordinated Im‐Ph. In the 1 : 1 FeTPPCl:Im‐Ph‐NH2 grafting solution used in this work, Im‐Ph‐NH2 is mostly uncoordinated. However, the formation constant for axiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The above physical characterization results show that a hydrophobic polymer layer was successfully generated on the electrode surface by applying the diazo-grafted formulation, i.e., the GraftFast process. Many recent works , already showed similar XPS results for successful grafting on GC. For example, Thomas et al achieved hydrophobic gas diffusion layers by diazonium grafting CF 3 -terminated amines on GC, and the XPS study demonstrated the successful grafting process.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The above physical characterization results show that a hydrophobic polymer layer was successfully generated on the electrode surface by applying the diazo-grafted formulation, i.e., the GraftFast process. Many recent works , already showed similar XPS results for successful grafting on GC. For example, Thomas et al achieved hydrophobic gas diffusion layers by diazonium grafting CF 3 -terminated amines on GC, and the XPS study demonstrated the successful grafting process.…”
Section: Resultsmentioning
confidence: 76%
“…XPS analysis further identified the hydrophobic coatings based on PEG or AGC, consistent with other reported work. Cyclic voltammetry (CV) of the redox probe again reflected the presence of hydrophobic layers that had already been established. As a result, in the 20 m LiTFSI electrolyte, the result showed that the free water reduction process is not observed with grafted GC electrodes by the LSV measurement, compared with a prominent free water reduction peak on a bare GC. Also, it excites a more negatively bound water reduction peak after grafting hydrophobic layers.…”
Section: Introductionmentioning
confidence: 93%